Ice Thickness‐Induced Variations in Effective Pressure and Basal Conditions Influence Seasonal and Multi‐Annual Ice Velocity at Sermeq Kujalleq (Jakobshavn Isbræ) - Xi Lu; Andrew Sole; Stephen J. Livingstone; Gong Cheng; Liming Jiang; Tom Chudley; Brice Noël; Daan Li (Geophysical Research Letters)
Abstract Acceleration of Sermeq Kujalleq has been linked to the retreat of its calving front. However, models consistently underestimate its ice‐flow variability, indicating that important physical processes might be ignored, which introduces uncertainties in projecting its future mass loss and sea‐level rise contribution. Using the Ice‐sheet and Sea‐level System Model, we simulate Sermeq Kujalleq from 2016 to 2022 constrained by sub‐monthly ice front positions. Changes in front position explain >76% of the velocity variations but with a spatially and seasonally varying misfit between modeled and observed velocities up to 30 km upstream. This misfit significantly correlates with variations in height above flotation within 10 km of the terminus. Incorporating these variations into the model by scaling the basal shear stress reduces the average misfit by over 90%. This indicates that seasonal variations in ice thickness‐induced effective pressure and basal conditions play a crucial role in controlling intra‐annual and longer‐term ice‐flow variations.